Characterizing the Effect of Intermittent Hypoxia on Hofbauer Cell Polarization and Placenta Vascularization, in vitro. - Corson, Abbey (Université d'Ottawa | University of Ottawa, 2024)
Background: Gestational parent (gesP) physical activity (PA) is associated with a plethora of health benefits that also provides an advantage to the fetus. Previous work from the Adamo Lab has found that the placenta-resident macrophage, termed Hofbauer cell (HBC), favours the anti-inflammatory phenotype compared to the pro-inflammatory phenotype in the placenta from physically active gesPs. A theorised effect of gesP PA is intermittent hypoxia (IH), but we do not know if this effect will polarize HBCs in a similar manner. Additionally, the implications on the downstream roles in the placenta are not known. Methods: The first objective of this thesis was to determine if IH influences HBCs in vitro. Primary human HBCs were cultured under two conditions: 5% O2 as a control and IH. Flow cytometry analysis was conducted to quantify pro- and anti-inflammatory HBCs. CD68 was used as a pan-macrophage marker and double positive CD86+/CD68+ or CD206+/CD68+ were identified as pro-inflammatory or anti-inflammatory, respectively. To assess the impact of IH on the functional purpose of HBCs, we performed a phagocytosis assay. HBC conditioned media was collected and analyzed with a cytokine array to determine the components of the media. The second aim was to use the HBC conditioned media and determine the independent or combined effect with IH on placenta angiogenesis. Human umbilical vein endothelial cells (HUVECs) were used in tube formation and migration assays under the following conditions: 8% O2 (control), 8% O2 with HBC conditioned media, IH, or combined (HBC conditioned media and IH). Results: No differences were found in the absolute number of pro-inflammatory (p = .832) or anti-inflammatory (p = .614) HBCs. The proportion of anti-inflammatory HBCs between the conditions did not differ significantly (p = .543) with a medium effect size, d = 0.55. Similarly, the proportion of pro-inflammatory HBCs had a negligible effect size, d = -0.143 , and did not differ significantly (p =.752) between the culture conditions. Phagocytosis percentage was also not distinct between the two culture conditions (p = .651). We detected differential regulation of cytokines depending on the oxygen tension. Identification of many pro-angiogenic, anti-angiogenic, and pleiotropic factors were identified in the conditioned media. Tube formation assays showed significantly shorter segments in the IH (p = .034) and IH/HBC ( p = .026) condition compared to the HBC condition. There was also a lower total mesh area in the IH (p = .038) and IH/HBC (p = .015) conditions compared to the HBC condition, along with less master segments in the IH (p = .039) condition compared to the HBC condition. Lastly, the master segments were shorter in both the IH (p = .038) and IHHBC (p = .028) conditions compared to the HBC condition. No significant differences were found between the control condition and the experimental conditions. IH and HBCs did not impact endothelial cell migration. Conclusions: In summary, IH may not be the main driver of differences in HBC polarization as previously noted by Goudreau et al. Our culture conditions maintained the heterogenous HBC population with some favouring of the pro-inflammatory phenotypes, suggesting that the culture conditions may not be fully representative of the in-vivo environment, a continued shortfall of in-vitro models. However, treatment with IH lead to different secretions from HBCs compared to the control. Therefore, IH appears to regulate HBC behaviour, subsequently influencing angiogenesis. While the impact of IH and HBCs on tube formation did not deviate significantly from baseline, our study shows that HBCs are master regulators of angiogenesis that do not override the protective mechanisms for vasculature formation under hypoxic conditions.
Keywords: Placenta; Physical activity; Hofbauer Cells; Angiogenesis; Gestational parent physical activity